PERLINDUNGAN HAK EKSLUSIF PENCIPTA MOTIF KEBAYA BORDIR DI KOTA DENPASAR - Dwi Parmana Putra, I Made; Dahana, Cok Dalem (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013, 2013)
Copyright is the exclusive right of the creator or assignee publish or reproduce creations or permit members without prejudice to the restrictions under the legislation in force. Problems arising from this paper how the implementation of the protection of exclusive rights kebaya embroidery motif creator in Denpasar. The method used in this paper is the method of Empirical Legal interviewing techniques from several sources. So we can conclude the protection of exclusive rights to the creator of kebaya embroidery motif in Denpasar men get automatic protection after kebaya motif is realized. Implementation of the protection of exclusive rights kebaya embroidery motif creator in Denpasar is the creator of kebaya embroidery motif found out right, in addition to moral rights, economic rights are met as remuneration in kebaya embroidery motifs made.
Keywords: Exclusive Rights, Legal Protection, Embroidery Kebaya